Generation of mature human myelomonocytic cells through expansion and differentiation of pluripotent stem cell–derived lin(–)CD34(+)CD43(+)CD45(+) progenitors - Choi, Kyung-Dal (American Society for Clinical Investigation, 2009)

(untitled)
Basic research into human mature myelomonocytic cell function, myeloid lineage diversification and leukemic transformation, and assessment of myelotoxicity in preclinical drug development requires a constant supply of donor blood or bone marrow samples and laborious purification of mature myeloid cells or progenitors, which are present in very small quantities. To overcome these limitations, we have developed a protocol for efficient generation of neutrophils, eosinophils, macrophages, osteoclasts, DCs, and Langerhans cells from human embryonic stem cells (hESCs). As a first step, we generated lin(–)CD34(+)CD43(+)CD45(+) hematopoietic cells highly enriched in myeloid progenitors through coculture of hESCs with OP9 feeder cells. After expansion in the presence of GM-CSF, these cells were directly differentiated with specific cytokine combinations toward mature cells of particular types. Morphologic, phenotypic, molecular, and functional analyses revealed that hESC-derived myelomonocytic cells were comparable to their corresponding somatic counterparts. In addition, we demonstrated that a similar protocol could be used to generate myelomonocytic cells from induced pluripotent stem cells (iPSCs). This technology offers an opportunity to generate large numbers of patient-specific myelomonocytic cells for in vitro studies of human disease mechanisms as well as for drug screening.